Manipulating laterality and polarity of transcranial direct current stimulation to optimise outcomes for anomia therapy in an individual with chronic Broca's aphasia. Issue 7 (3rd July 2018) - Sandars, Margaret; Cloutman, Lauren; Woollams, Anna M.
ABSTRACT: Background : Previous research indicates that combining behavioural therapy with transcranial direct current stimulation (tDCS) may be more effective than therapy alone in increasing naming ability in stroke survivors with chronic anomia. Anodal (excitatory) stimulation targeting left perilesional areas and/or cathodal (inhibitory) stimulation targeting right contralesional areas may particularly benefit non-fluent patients with localised damage to the left frontal lobe. However, studies have yet to systematically compare the effects of varying the laterality and polarity of tDCS within individual patients in order to determine optimal stimulation parameters. Aims : The primary purpose of the current study was to determine which tDCS parameters would result in the greatest improvements in naming ability in an individual (JSc) with chronic Broca's aphasia (9 years post-stroke) due to a left frontal lesion. A range of secondary outcome measures were also collected to explore the potential effects of therapy on JSc's connected speech, emotional well-being, and communicative effectiveness. Methods & Procedures : Following baseline naming assessment, JSc completed six, 4-week long cycles of therapy, each involving a different stimulation condition: four active (perilesional anodal, perilesional cathodal, contralesional anodal, and contralesional cathodal) and two sham control conditions (perilesional and contralesional). In the first week of each cycle, he completed three, 20-min therapy sessions, during which he carried out a personalised picture name repetition therapy task at the same time as receiving tDCS. Naming ability was measured before, immediately after, 1 week after, and 3 weeks after each week of therapy. The secondary outcome measures were completed before, 1 week after, and 3 weeks after each week of therapy. Outcomes & Results : Naming accuracy immediately after stimulation increased significantly more following perilesional anodal stimulation than following perilesional sham stimulation, and this effect remained significant at 3 weeks post-therapy. Treatment effects on the secondary outcome measures were less consistent. Conclusions : The results agree with previous work demonstrating the importance of activation in left frontal perilesional regions for accurate picture naming in stroke survivors with non-fluent aphasia. We have shown that the effectiveness of a total of 1 h of behavioural anomia therapy can be significantly increased when combined with perilesional anodal tDCS and demonstrated the feasibility of a longitudinal, repeated measures design with multiple outcome measures. Greater understanding of the optimal tDCS parameters to enhance anomia therapy outcomes in individual patients with differing lesion and behavioural profiles may one day assist with the translation of therapy plus tDCS protocols into everyday clinical practice.